Dietary Protein Requirement of Juvenile Fuxian Minnow, Anabarilius grahami. Issue 2 (3rd April 2013) - Deng, Junming; Zhang, Xi; Tao, Linli; Rong, Hua; Bi, Baoliang; Kang, Bin
Abstract A 10‐wk experiment was conducted to determine the optimum dietary protein requirement of juvenile Fuxian minnow, Anabarilius grahami (initial average weight 4.14 g). Five isocaloric diets were formulated to contain graded levels of protein (29, 34, 39, 44, and 49%). Each diet was fed to triplicate groups of fish in a recirculating rearing system maintained at 17–21 C. Feed intake of fish fed the 39 and 44% protein diets was significantly higher than that of fish fed the 29, 34, and 49% protein diets (P < 0.05). Weight gain and protein gain significantly increased with increasing dietary protein level up to 39% (P < 0.05), but no significant differences were observed among fish fed the 39, 44, and 49% protein diets (P > 0.05). In contrast, feed conversion ratio decreased with increasing dietary protein level up to 39%. Protein retention efficiency or protein efficiency ratio generally increased with increasing dietary protein level up to 39%, and then the value gradually decreased thereafter. Broken‐line regression analysis showed that the optimum dietary protein requirement for maximum weight gain of juvenile A. grahami under the experimental conditions was 38.6% (equivalent to ca. 33.0% estimated digestible protein).